Daya Saing Ekspor Pisang Indonesia di Negara Tujuan Ekspor Periode 2000-2019 (Jurnal Agribisnis Indonesia, 2022)
Indonesian banana is one of the leading commodities of the tropical fruit group that has been traded for a long time. One of the most important components of the economy is exporting. Indonesian banana production contributes in the world and taking the third position, but is not balanced with Indonesia's contribution to banana exports in the world. This study analyzed competitiveness with the comparative and competitive advantage approach of Indonesian banana using secondary data in the period 2000-2019. The research method used descriptive-quantitative with Revealed Comparative Advantage (RCA), Export Product Dynamic (EPD), and Porter's Diamond. The results of the analysis RCA showed that Indonesian banana only have strong competitiveness in the Malaysian market. Indonesian banana competitiveness position in the Malaysian market is in the position of rising star and falling star in the Singapore, Japan and Saudi Arabian markets. The results of the last analysis used Porter's Diamond found weaknesses in the factor conditions related to human resources, capital, science and technology, demand conditions as well as strategy, structure, and competition. Therefore, it is necessary to make efforts to increase the productivity and quality of banana produced, market research in competing countries, consumer preferences in world markets, and provide counseling as well as socialization and product diversification.